2017
DOI: 10.3389/fendo.2017.00341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Preclinical Advances in Gastroenteropancreatic Neuroendocrine Tumor Therapy

Abstract: The molecular events leading to gastroenteropancreatic neuroendocrine tumor (GEP-NET) formation are largely unknown. Over the past decades, systemic chemotherapies have been replaced by therapies directed at particular molecular targets such as the somatostatin receptors, mTOR complexes or proangiogenic molecules. These approaches have demonstrated some success in subtypes of this heterogeneous tumor group, but responses are still widely varied. This review highlights the clinical trials ongoing for neuroendoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Given the advancements with novel therapies such as PRRT, it is time to test if this therapy can be combined with other established therapies in the field of NETs. There are ongoing trials where PRRT is being combined with capecitabine for GEP NET patients, and another trial where PRRT is being combined with capecitabine and temozolomide in midgut and pancreatic NET patients [101].…”
Section: Discussionmentioning
confidence: 99%
“…Given the advancements with novel therapies such as PRRT, it is time to test if this therapy can be combined with other established therapies in the field of NETs. There are ongoing trials where PRRT is being combined with capecitabine for GEP NET patients, and another trial where PRRT is being combined with capecitabine and temozolomide in midgut and pancreatic NET patients [101].…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized trial comparing lanreotide with placebo in 88 patients demonstrated that lanreotide was associated with significantly higher rates of PFS at 24 months – 65.1% (95% CI, 54.0–74.1) compared to 33.0% (95% CI, 23.0–43.3) in the placebo group ( P < 0.001) (13). In addition to control of tumor growth, SSAs have been shown to highly effective in controlling symptoms of hormone oversecretion in over half of patients (14). Our patient is currently receiving LAR octreotide as an adjunct after surgery for the residual disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies targeting VEGF (sunitinib, pazopanib, cabozantinib and axitinib) and mTOR (everolimus) have been used with promising results in NETs originating from other sites of the body (primarily gastrointestinal NETs and pancreatic NETs). Sunitinib was FDA approved for advanced pancreatic NETs after a phase III study showed PFS advantage compared to placebo (14). A summary of clinical studies with targeted agents in the treatment of advanced NETs is provided in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…There have been important advancements in cancer therapy over the past few years, especially in the area of neuroendocrine tumors. Systemic chemotherapy is beginning to be replaced by therapeutics specifically targeted at molecular entities, which is having an impact on agent selection, patient management, and long-term outcomes [1].…”
Section: Introductionmentioning
confidence: 99%